INTERNALISASI NILAI-NILAI KEISLAMAN TERHADAP PERKEMBANGAN ANAK DI SEKOLAH DASAR MUHAMMADIYAH KRIYAN JEPARA - Toni Ardi Rafsanjani; Muhammad Abdur Razaq (Universitas Muhammadiyah Surakarta, 2019)
This study aims to analyze and describe the internalization of Islamic religious education values on the students’ development at Muhammadiyah Elementary School of Kriyan Jepara. This is qualitative research, taking the background of Muhammadiyah Elementary School of Kriyan Jepara. The data collection methods are indept interviews, participant observation and documentation. Data analysis is carried out by descriptive data analysis techniques which included three concurrent activities, data reduction, data presentation, and conclusion drawing. The results of this study are 1) Internalizing the values of Islamic religious education by planting theory / knowledge is strengthened by the word of Allah SWT and the hadith of the Prophet Muhammad; 2) Internalization of the values of Islamic religious education is carried out with exemplary stories and wisdom of life; 3) Internalization of the values of Islamic religious education is carried out by learning religious and public materials that are interconnected through the synergy of the national education curriculum and Kemuhammadiyahan; 4) Internalization of the values of Islamic religious education is carried out through programs of intellectuality, spirituality and humanity. While the form of success is the habit of piety to shape students into progressive students. The students carry out the internalization effort because trusting and adhering to it as a provision brings to mind peace and remembrance. Internalization effort is successfully carried out not because of a hard emphasis on education, but an effort to habituate the values of Islamic religious education that are religious humanists and carried out as often as possible, both in the school environment and at home.Abstrak: Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan internalisasi nilai-nilai pendidikan agama Islam terhadap perkembangan anak di SD Muhammadiyah Kriyan Jepara. Penelitian ini adalah penelitian kualitatif, dengan mengambil latar SD Muhammadiyah Kriyan Jepara. Metode pengumpulan datanya adalah indept interviews, observasi partisipan dan dokumentasi. Analisis data dilakukan dengan teknik analisis data diskriptif yang mencakup tiga kegiatan bersamaan, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini adalah 1) Internalisasi nilai-nilai pendidikan agama Islam dengan penanaman teori/ ilmu yang dikuatkan dengan firman Allah SWT dan hadis Nabi Muhammad SAW; 2) Internalisasi nilai-nilai pendidikan agama Islam dilakukan dengan kisah-kisah teladan dan hikmah kehidupan; 3) Internalisasi nilai-nilai pendidikan agama Islam dilakukan dengan pembelajaran materi agama dan umum yang saling terkoneksi melalui sinergitas kurikulum pendidikan nasional dan Kemuhammadiyahan; 4) Internalisasi nilai-nilai pendidikan agama Islam dilakukan melalui program pembiasaan intelektualitas, spiritualitas dan humanitas. Sedangkan wujud keberhasilannya adalah pembiasaan kesalehan membentuk siswa menjadi pelajar yang berkemajuan. Para siswa melaksanakan upaya internalisasi itu karena memercayai dan menganutnya sebagai bekal membawa pada ketenangan pikir dan zikir. Upaya internalisasi berhasil dilakukan bukan karena penekanan pendidikan yang keras, melainkan usaha pembiasaan nilai-nilai pendidikan agama Islam yang humanis religius dan dilakukan sesering mungkin, baik di lingkungan sekolah maupun di rumah.